Co-existing polysaccharides affect the systemic exposure of major bioactive ingredients in Chang-Kang-Fang, a multi-herb prescription for treatment of irritable bowel syndrome. (15th November 2022) - Zhong, Ping; Zhou, Jing; Fan, Yan-Ting; Guo, Meng-Fei; Zhu, He; Zhou, Shan-Shan; Zhu, Jin-Hao; Zhang, Huan-Huan; Zhou, Gui-Rong; Miao, Xing-Long; Li, Song-Lin; Mao, Qian
Abstract: Ethnopharmacological relevance: Chang-Kang-Fang (CKF) is a traditional Chinese herbal formula used for treatment of irritable bowel syndrome (IBS) in China. Decoction is the administration form of CKF in clinical practice. Previously, CKF has been confirmed with activities of releasing pain and reversing disorders of intestinal propulsion. And alkaloids, monoglycosides, chromones were found as the main bioactive components potentially contributing to the efficacy of CKF. Polysaccharide was also a major constituent in CKF. But if and how polysaccharides influence the systemic exposure of bioactive components in CKF is unknown. Aim of the study: In this study, we aimed to demonstrate the contribution of the co-existed polysaccharides on the systemic exposure of the major bioactive components from CKF in normal and IBS model rats. Materials and methods: An UPLC-TQ-MS with multiple reaction monitoring (MRM) scan method was developed and validated for quantifying six major small molecular bioactive ingredients of CKF in the plasma samples, including magnoflorine (MAG), berberine (BBR), albiflorin (ALB), paeoniflorin (PAE), 5- O -methylvisamminol (5-OM) and prim - O -glucosylcimifugin (POG). The rats received CKF decoction (CKF) and CKF small molecule portion (knockout of polysaccharides, CKFSM), respectively. IBS model rats were induced by daily bondage and gavage of Sennae Folium decoction (derived from the leaf of Cassia angustifolia Vahl). The effects of the co-existing polysaccharides on the pharmacokinetic parameters of six small molecular bioactive components in normal and IBS model rats were systematically evaluated. The potential gut microbiota involved mechanisms of the effects was validated by broad-spectrum antibiotic (ABX) treatment. Results: The selectivity, precision, accuracy, recovery and matrix effect of the established quantification method were all within acceptable limits of biological sample. In normal rats, the co-existing polysaccharides significantly reduced the AUC(0-t) of MAG and PAE compared with CKFSM group. The Cmax and AUC(0-t) of other four compound were not influenced by co-existing polysaccharides. However, in IBS model rats, compared with CKFSM group, the Cmax and AUC(0-t) of the six ingredients significantly increased in CKF group. For CKF + ABX group, the Cmax of six ingredients decreased significantly when compared with CKF group, and the AUC(0-t) of MAG, BBR, ALB, PAE also reduced with significant differences. Conclusions: A reliable and sensitive UPLC-TQ-MS method was successfully developed and validated for evaluating influence of co-existing polysaccharides on pharmacokinetic behavior of six major small molecules components in CKF. The co-existing polysaccharides enhanced the systemic exposure of six bioactive small molecules in CKF under IBS pathological state potentially via gut microbiota involvement. Graphical abstract: Image 1 Highlights: UPLC-TQ-MS method was established and validated for investigating the systemic exposure of six bioactive ingredients in CKF. Co-existing polysaccharides enhanced the systemic exposure of major bioactive ingredients in CKF under IBS pathological state. Gut microbiota involvement might be responsible for the enhancement of the polysaccharides on the systemic exposure of major bioactive ingredients in CKF.